SOBAT GESIT (SELURUH KELUARGA TERLIBAT GERAKAN STOP STUNTING): INOVASI APLIKASI PENCEGAHAN STUNTING - Elisa Christiana; Cantika Iva; Cucun Setya F; Hilmah N; Agoesta Pralita; Edy Suryadi; Taufiqur R; Nur Iszakiyah (Jurnal Abdimas Bina Bangsa, 2024)
The 2022 Indonesian Nutrition Status Survey (SSGI) reports that the Pamekasan District Health Service has succeeded in reducing the incidence of stunting significantly, from 38.6% in 2021 to 8.1%. The next urgency is to maintain these positive achievements and ensure that there are no more cases of stunting, so an innovative idea is needed in the form of Sobat Gesit (all family members are involved in the stop stunting movement). The aim of the Agile Buddy application is to serve as a medium for public education about stunting prevention efforts and to assist the government in reducing stunting rates. The development of the Agile Buddy application is preceded by a preliminary study in the form of a literature study and determining the software model to be used. The features that will be available in this application consist of agile father, agile mother, agile child, stunting PIC features, and report stunting. It is hoped that this application can help prevent and reduce stunting rates according to the target in 2024 to create a healthy and high-quality young generation